IMPLEMENTATION OF THE PRINCIPLE OF BALANCE IN INCLUDING STANDARD CLAUSES IN BANK CREDIT AGREEMENTS - Shely, Shely; Sri Astutik (Cahaya Ilmu Bangsa, 2023)
In the context of consumer protection, the role of the principle of balance in a bank credit agreement is crucial. This principle emphasizes the need for equal and balanced positions of the parties involved, particularly the Business Entity (Creditor) and the Consumer (Debtor). However, in practice, cases are often found where there is an imbalance between the Creditor and Debtor. The Credit Agreement is prepared by the Creditor and contains standard clauses and stipulations of standard regulations that will be agreed upon together while still considering the principle of balance in the positions of both the Creditor and Debtor. The research aimed to know, understand, and analyze the legal aspects of consumer protection, with a specific focus on the implementation of the principle of balance in a credit agreement. The research methodology employed was doctrinal legal research, using legislative and conceptual approaches. The research findings revealed that certain provisions in the bank credit agreement did not adhere to the elements of the principle of balance, resulting in the bank appearing to dominate and exert pressure on the other party. Therefore, a credit agreement should not only apply the principle of balance, but also consider the principles of benefit, justice, and legal certainty for all parties involved.